Hydrogen electrooxidation under conditions of high mass transport in room-temperature ionic liquids and the role of underpotential-deposited hydrogen - Goodwin, Sean E.; Walsh, Darren A. (American Chemical Society, 2016)
The hydrogen oxidation reaction (HOR), an electrocatalytic reaction of fundamental and applied interest, was studied in the protic ionic liquid (PIL) diethylmethylammonium trifluoromethanesulfonate, [dema][TfO], at Pt electrodes using rotating disk electrode (RDE) and ultramicroelectrode (UME) voltammetry. A steady-state HOR current is observed during RDE voltammetry at overpotentials > 50 mV but an additional plateau is observed in the overpotential region 50-200 mV when using UMEs. The difference in voltammetric responses is attributed to higher rate of mass transport to the UME than to the RDE. Three models have been used to fit the experimental data. The first is a dual-pathway model, which assumes that the Tafel-Volmer and Heyrovsky-Volmer pathways are both active over the potential range of interest and no blockage of catalytic sites occurs during the reaction. The second is a dual-pathway model, which assumes that reaction intermediates block access of H2 to catalytic sites. The third is based on the premise that underpotential-deposited hydrogen atoms (Hupd) can block adsorption and electrooxidation of H2 at the Pt surface. While each model fits the polarisation curves reasonably well, detailed analysis suggests that the Hupd- blocking model describes the responses better. To the best of our knowledge, this work is the first to demonstrate the advantages of UME voltammetry over RDE voltammetry for studying electrocatalytic reactions in PILs, and the first to show that Hupd can inhibit an electrocatalytic reactions in an ionic liquid, a factor that may become important as the technological applications of these liquids increase.